Double-drug-loading controlled-release bone repair composite scaffold material and preparation method thereof

By using a composite scaffolding material composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, loading icariin and Anabolin BⅡ, the shortcomings of existing bone repair materials in terms of mechanical properties, biocompatibility and drug loading volume are solved, and efficient bone repair results are achieved.

CN119868658APending Publication Date: 2025-04-25SUZHOU TRADITIONAL CHINESE MEDICINE HOSPITAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410957466.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing bone repair materials have shortcomings in mechanical properties, biocompatibility and drug loading, which are difficult to effectively promote bone repair.

Method used

The dual-load drug controlled-release bone repair composite scaffold material consisting of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose is used. Iciaris is loaded in mesoporous bioactive glass nanoparticles, and Anathrin is loaded on the composite scaffold, so that the load and controlled release of drugs are achieved through the mesoporous structure.

Benefits of technology

This material has both the toughness of an organic material, the strength and biological activity of an inorganic material, and realizes the controlled release of two drugs, significantly promotes the bone repair process, and the drug loading is high and the sustained release effect is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004949277730000101
    Figure BDA0004949277730000101
  • Figure BDA0004949277730000131
    Figure BDA0004949277730000131
  • Figure BDA0004949277730000141
    Figure BDA0004949277730000141
Patent Text Reader

Abstract

The invention discloses a double-drug-loading controlled-release bone repair composite scaffold material, the composite scaffold is composed of mesoporous bioactive glass nanoparticles and silk fibroin, the loaded drugs are icariin and timosaponin BII, the icariin is loaded in the mesoporous bioactive glass nanoparticles, the silk fibroin is loaded in the mesoporous bioactive glass nanoparticles, and the icariin and the timosaponin BII are loaded in the mesoporous bioactive glass nanoparticles. The drug controlled release sequence is that timosaponin BII is rapidly released in the early stage and icariin is slowly released in the later stage. The composite scaffold has good mechanical properties and biocompatibility, is well combined with natural bones, is an effective material for bone repair, and can realize loading and controlled release of drugs, dual-loading controlled release icariin and timosaponin BII can make up for the defects of scaffold material performance and play a role in eliminating inflammation, and the composite scaffold has a good application prospect. The bone repair is further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to a dual-drug-loaded controlled-release bone repair composite scaffold material and a preparation method thereof. Background Art

[0002] Bone tissue itself has a certain self-repair and regeneration ability, but it is difficult for bone tissue to repair itself due to more serious bone defects or fractures caused by trauma, infection and other problems, and it is necessary to use certain medical means for bone repair. Among bone repair materials, autologous bone is the gold standard, but its supply is limited and the quality of bone supply is unstable, which is difficult to meet clinical needs. Therefore, it is of great significance to develop suitable bone repair materials. Ideal bone repair materials should have good mechanical properties and biocompatibility, have strong bonding strength with natural bone, and have osteoinduction and osteoconduction effects. Artificially synthesized bone repair materials are mainly divided into metal materials, polymer materials, inorganic materials and organic / inorganic composite materials. According to the structure and components of natural bone, organic / inorganic composite materials can restore the morphology and function of bone tissue to the maximum extent. They have both the strength and biological activity of inorganic materials and the toughness of organic components. They are one of the ideal materials for bone repair scaffolds. In addition, loading drugs in bone repair scaffolds can make up for the performance deficiencies of scaffold materials and further improve the repair effect of scaffolds. Summary of the invention

[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a dual-drug loaded controlled-release bone repair composite scaffold material.

[0004] Technical solution: A dual-drug loaded controlled-release bone repair composite scaffold material, composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold. Preferably, the method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol and shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix to obtain a uniform mixed solution; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly drip the Anemarrhena saponin BⅡ solution into the composite scaffold until it is completely adsorbed to obtain a dual-drug loaded controlled-release bone repair composite scaffold material. Preferably, the method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. Centrifuge the sol prepared in step S12 to obtain a white precipitate, wash, dry, and then calcine to obtain mesoporous bioactive glass nanoparticles. Preferably, the concentration of icariin in the solution prepared in step S1 is 0.45-0.55 mg / mL. Preferably, in the mesoporous bioactive glass nanoparticles prepared in the solution in step S3, the mass ratio of nanocellulose to silk fibroin is 1:4-12:22.5-31.5. Preferably, the concentration of the Anemarrhena saponin BⅡ solution in step S5 is 35-45 ng / μL. Preferably, the drug loading of icariin in the composite scaffold is 14-27%, and the drug loading of anemarrhena saponin BII is 18-27%. Preferably, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution in step S11 is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 5.5-6.5 mg / mL. Preferably, in step S12, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate and ethyl orthosilicate is 1.3:3.3-3.4:15.0-15.1. Preferably, the calcination temperature in step S13 is 630-670° C., the heating rate is 1-3° C. / min, and the holding time is 2-4 h. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The bone repair composite scaffold material of the present invention uses silk fibroin and mesoporous bioactive glass nanoparticles as scaffolds and is loaded with drugs icariin and anemarrhena saponin BⅡ, thereby achieving controlled release of the two drugs and effectively promoting bone repair. As a natural polymer material, silk fibroin has a structure similar to collagen fibers in natural bones, and has good mechanical properties and cell compatibility, which can promote the adhesion and growth of fibroblasts. Mesoporous bioactive glass nanoparticles are improved on the basis of bioactive glass. They not only have high bioactivity, bone binding strength and good degradability, but also have nanoscale pore size and large specific surface area. They can release silicon calcium ions to stimulate osteogenic gene expression and promote cell differentiation. They are an ideal inorganic material for bone repair. The bone repair composite scaffold prepared by using silk fibroin and mesoporous bioactive glass nanoparticles can have both good biocompatibility, mechanical properties and good degradability. In addition, the mesoporous structure of mesoporous bioactive glass can realize the loading and controlled release of drugs, making up for the shortcomings of bone repair scaffolds. Compared with traditional drug-loading media, mesoporous bioactive glass has a higher drug loading capacity and can achieve good drug sustained release effect without surface modification. It is more stable and long-lasting as a drug carrier. Compared with the prior art, the present invention has the following advantages and positive effects: The present invention adopts silk fibroin, nanocellulose and mesoporous bioactive glass nanoparticles to prepare a bone repair composite scaffold, which has both the toughness of organic materials and the strength and bioactivity of inorganic materials, and is an ideal bone repair scaffold material. The present invention utilizes the mesoporous structure of mesoporous bioactive glass to achieve drug loading and controlled release. Compared with traditional drug carriers, the drug loading capacity is higher, the controlled release effect is more stable, and the drug loading method is simple, controllable and easy to operate. The present invention double-loads the drugs icariin and anemarrhena saponin BII in the bone repair scaffold, and controls the release of the two drugs, thereby better promoting bone repair. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Embodiment 2: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (20.4±0.01)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution in step S11 is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Embodiment 3: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (14.3±0.036)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Embodiment 4: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (26.7±0.032)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Embodiment 5: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (18.02±0.055)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. In order to further illustrate the technical effect of the present invention, the present invention also provides a comparative example, which is as follows: Comparative Example 1: A drug-loaded composite stent material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles; The preparation method of the drug-loaded composite stent material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1 and stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is lyophilized and then washed and dried to obtain a drug-loaded composite stent material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading amount of icariin in the composite scaffold is (26.5±0.014)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Comparative Example 2: A drug-loaded composite scaffold material, composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, with Anemarrhena saponin BⅡ loaded on the composite scaffold; The preparation method of the drug-loaded composite stent material comprises the following steps: S1. Prepare a suspension of mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix. The mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27 to obtain a uniform mixed solution; S2. The mixed solution prepared in step S1 is freeze-dried and then washed and dried to obtain a composite scaffold material; S3. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite stent until it is completely adsorbed to obtain a drug-loaded composite stent material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading amount of Anemarrhena saponin BⅡ in the composite scaffold is (21.9±0.015)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Comparative Example 3: A dual-drug-loaded composite scaffold material, composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, with icariin and anemarrhena saponin BⅡ loaded on the composite scaffold; The preparation method of the dual-drug loaded composite stent material comprises the following steps: S1. Prepare a suspension of mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix. The mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27 to obtain a uniform mixed solution; S2. The mixed solution prepared in step S1 is freeze-dried and then washed and dried to obtain a composite scaffold material; S3. Slowly dripping a 0.5 mg / mL icariin solution into the composite scaffold until it is completely adsorbed to obtain a composite scaffold material loaded with icariin; S4. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite stent until it is completely adsorbed to obtain a dual-drug loaded composite stent material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Table 1 In vitro cumulative release rate of drugs in Example 1 and Comparative Example 3 Comparative Example 4: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (11.5±0.027)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Comparative Example 5: A dual-drug-loaded controlled-release bone repair composite scaffold material, which is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, wherein icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold; the preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix, the mass ratio of mesoporous bioactive glass nanoparticles, nanocellulose and silk fibroin is 1:8:27, and a uniform mixed solution is obtained; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly dripping a 40 ng / μL solution of Anemarrhena saponin BⅡ into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate to tetraethyl orthosilicate being 1.30:3.39:15.04, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. The sol prepared in step S12 is centrifuged to obtain a white precipitate, which is washed, dried, and then calcined at a temperature of 650° C., a heating rate of 2° C. / min, and a holding time of 3 h to obtain mesoporous bioactive glass nanoparticles; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (11.43±0.072)%; In step S11, the pH of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 6 mg / mL. Comparative Example 6: A dual-drug-loaded controlled-release bone repair composite scaffold material, composed of hydroxyapatite and silk fibroin microspheres, icariin loaded in the silk fibroin microspheres, and anemarrhena saponin BⅡ loaded on the composite scaffold; The preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol, the concentration of icariin is 0.5 mg / mL, shake until completely dissolved to obtain a clear solution; S2. mixing the solution prepared in step S1 with the silk fibroin solution, placing the mixed solution on a high-voltage electrostatic spray device to prepare and collect microspheres, and freeze-drying to obtain icariin-silk fibroin microspheres; S3. mixing icariin-silk fibroin microspheres with hydroxyapatite, wherein the mass ratio of silk fibroin to hydroxyapatite is 2:3, adding phosphate buffer and ultrasonically shaking to obtain a suspension; S4. The suspension prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Dissolve Anemarrhena saponin BⅡ in phosphate buffer at a concentration of 40 ng / μL, and slowly drip into the composite scaffold until it is completely adsorbed to obtain a dual-drug-loaded controlled-release bone repair composite scaffold material; The drug loading of icariin in the composite scaffold is (26.5±0.014)%, and the drug loading of anemarrhena saponin BⅡ is (21.9±0.015)%; The pH of the phosphate buffer in steps S3 and S5 is 6.8. 1. Establishment of the distal femur fracture model in mice 1. Experimental animals: 10-week-old SAMP6 mice; 2. Anesthetize all mice; 3. Modeling: Take the lateral approach to the patella, turn the patella over, expose the intercondylar fossa of the femur, drill a hole, insert a 0.4mm injection needle into the medullary cavity, and then use a 0.2mm elastic guide wire for insertion. After removing the guide wire, use an electric saw to create a supracondylar femoral fracture, place the guide wire again, and then insert a 0.5mm intramedullary fixation device. Cut the stent into small pieces and implant them so that they are evenly distributed around the broken end. 2. Drug treatment after fracture in mice Grouping: The mice were randomly divided into 12 groups, 10 mice in each group; Blank control group (control group: no stent implanted after fracture); icariin-loaded group (Comparative Example 1); timosaponin BⅡ-loaded group (Comparative Example 2); double-loaded icariin and timosaponin BⅡ group (Comparative Example 3); double-loaded controlled-release icariin and timosaponin BⅡ group (Examples 1-5, Comparative Examples 4-5, different drug loading amounts); double-loaded controlled-release icariin and timosaponin BⅡ groups with different stents (Comparative Example 6). 3. Evaluation of therapeutic effects in mouse fracture model 1. Inflammatory index test Enzyme-linked immunosorbent assay was used to measure the levels of interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in serum and local tissues using kits; 2. Assessment of healing speed Ordinary X-rays were used to observe the callus growth at the fracture end at regular intervals to monitor and evaluate the callus growth. In vivo sequential fluorescent labeling technology was used to subcutaneously inject 25 mg / kg tetracycline hydrochloride and 5 mg / kg calcein into the back of the animals 14 and 13 days before sacrifice, and 4 and 3 days before sacrifice, respectively, for dual fluorescent labeling to measure the dynamic parameters of bone tissue. The dynamic parameters included single fluorescence perimeter, dual fluorescence perimeter and dual fluorescence interval, and the mineralization deposition rate (μm / d) and bone formation rate (μm / d) were calculated. Silver nitrate staining was commonly used to observe the calcium nodules of osteoblasts (calcium nodules were stained black or brown-black), and the number of osteoblasts was indirectly calculated through image analysis. 3. Assessment of healing quality μ-CT scans were used to evaluate the changes in trabecular microstructure at the femur of the fracture end; dual-energy X-ray absorptiometry was used to measure bone density (g / cm 2 ); Hematoxylin-eosin staining and Masson staining were used for histopathological evaluation: the matching of new bone formation and material degradation was detected, and the balance between bone resorption and bone formation was comprehensively observed. Table 2 Parameters for evaluating the therapeutic effects of the embodiments and comparative examples In summary, the dual-drug-loaded controlled-release bone repair composite scaffold material prepared by the present invention has better therapeutic effect on mouse fractures, the inflammation test index of the embodiment is lower, the bone healing speed is faster, the bone healing quality is better, and the therapeutic effect is significantly better than that of the comparative example.

Claims

1. A dual-drug-loaded controlled-release composite scaffold material for bone repair, characterized in that: The bone repair composite scaffold is composed of mesoporous bioactive glass nanoparticles, silk fibroin and nanocellulose, icariin is loaded in the mesoporous bioactive glass nanoparticles, and anemarrhena saponin BⅡ is loaded on the composite scaffold.

2. The method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 1, characterized in that: The preparation method of the dual-drug-loaded controlled-release bone repair composite scaffold material comprises the following steps: S1. Dissolve icariin powder in ethanol and shake until completely dissolved to obtain a clear solution; S2. adding mesoporous bioactive glass nanoparticles to the solution prepared in step S1, stirring to allow the mesoporous bioactive glass nanoparticles to fully adsorb icariin, collecting the particles after the reaction by centrifugation, washing and freeze-drying to obtain icariin-mesoporous bioactive glass nanoparticles; S3. Prepare a suspension of icariin-mesoporous bioactive glass nanoparticles, stir and mix with the nanocellulose solution, and then add the silk fibroin solution and stir and mix to obtain a uniform mixed solution; S4. The mixed solution prepared in step S3 is freeze-dried and then washed and dried to obtain a composite scaffold loaded with icariin; S5. Slowly drip the Anemarrhena saponin BⅡ solution into the composite scaffold until it is completely adsorbed to obtain a dual-drug loaded controlled-release bone repair composite scaffold material.

3. The dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 1, characterized in that: The method for preparing the mesoporous bioactive glass nanoparticles comprises the following steps: S11. The hexadecyltrimethylammonium bromide was added to the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution, heated in an oil bath and stirred until the hexadecyltrimethylammonium bromide was completely dissolved to obtain a clear solution; S12. Adding tetraethyl orthosilicate, triethyl phosphate and calcium nitrate tetrahydrate to the solution prepared in step S11 in sequence, stirring until completely dissolved, and then performing a hydrolysis-condensation reaction to obtain a white uniform sol; S13. Centrifuge the sol prepared in step S12 to obtain a white precipitate, wash, dry, and then calcine to obtain mesoporous bioactive glass nanoparticles.

4. The method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 2, characterized in that: The concentration of icariin in the solution prepared in step S1 is 0.45-0.55 mg / mL.

5. The method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 2, characterized in that: In the solution prepared in step S3, the mass ratio of nanocellulose to silk fibroin in the mesoporous bioactive glass nanoparticles is 1:4-12:22.5-31.

5.

6. The method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 2, characterized in that: The concentration of the Anemarrhena saponin BⅡ solution in step S5 is 35-45 ng / μL.

7. The method for preparing the dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 2, characterized in that: The drug loading amount of icariin in the composite stent is 14-27%, and the drug loading amount of anemarrhena saponin BII is 18-27%.

8. The dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 3, characterized in that: In step S11, the pH value of the hydrochloric acid-tris(hydroxymethyl)aminomethane buffer solution is 8.0, and the concentration of hexadecyltrimethylammonium bromide is 5.5-6.5 mg / mL.

9. The dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 3, characterized in that: In step S12, the mass ratio of triethyl phosphate, calcium nitrate tetrahydrate and ethyl orthosilicate is 1.3:3.3-3.4:15.0-15.

1.

10. The dual-drug-loaded controlled-release bone repair composite scaffold material according to claim 3, characterized in that: The calcination temperature in step S13 is 630-670° C., the heating rate is 1-3° C. / min, and the heat preservation time is 2-4 h.